2013
DOI: 10.1371/journal.pone.0066666
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the First Escherichia coli Strain Carrying NDM-1 Gene in China

Abstract: New Delhi metallo-β-lactamase-1 (NDM-1), an acquired class B carbapenemase, is a significant clinical threat due to its extended hydrolysis of β-lactams including carbapenems. In this study, we identified the first confirmed clinical isolate of Escherichia coli BJ01 harboring bla NDM-1 in China. The isolate is highly resistant to all tested antimicrobials except polymyxin. bla NDM-1, bla CTX-M-57, and bla TEM-1 were identified in the isolate. bla NDM-1 was transferable to E. coli EC600 and DH5α in both plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 36 publications
1
32
1
2
Order By: Relevance
“…and E. faecium. Although there have been several molecular level researches on the genetic context of bla NDM-1 , there are limited recent studies on the epidemiology of bla NDM-1 -containing isolates [1,2,9,13,16,23]. Compared with previous reports [2,13], the present study demonstrated that the numbers and species of bla NDM-1 in family Enterobacteriaceae have significantly increased in China, and include Klebsiella pneumoniae, Enterobacter cloacae, Enterobacter aerogen and Citrobacter freundii.…”
Section: Discussioncontrasting
confidence: 56%
“…and E. faecium. Although there have been several molecular level researches on the genetic context of bla NDM-1 , there are limited recent studies on the epidemiology of bla NDM-1 -containing isolates [1,2,9,13,16,23]. Compared with previous reports [2,13], the present study demonstrated that the numbers and species of bla NDM-1 in family Enterobacteriaceae have significantly increased in China, and include Klebsiella pneumoniae, Enterobacter cloacae, Enterobacter aerogen and Citrobacter freundii.…”
Section: Discussioncontrasting
confidence: 56%
“…The sporadic emergence of NDM-1-producing E. coli and K. pneumoniae in mainland China has been reported in two recent studies (12,13). Additionally, several cases of NDM-1-producing CRE reported from Hong Kong and Taiwan were also epidemiologically linked to mainland China (40)(41)(42).…”
Section: Resultsmentioning
confidence: 85%
“…Carbapenem resistance in Enterobacteriaceae in China has been mainly associated with Klebsiella pneumoniae carbapenemases (KPCs), such as KPC-2, and MBLs (such as IMP-4) other than NDM-1 (10,11). NDM-1-mediated carbapenem resistance in Enterobacteriaceae in China has been rarely reported; so far there have been only two confirmed cases of NDM-1-producing K. pneumoniae and E. coli infections in China (12,13). A recent study detected a high infection rate (14.8%) of NDM-1-producing bacteria in clinical fecal samples from multiple hospitals in China, but none of the NDM-1-carrying bacteria belonged to Enterobacteriaceae (14).…”
mentioning
confidence: 99%
“…Indeed, CTX-M-15-producing E. coli ST410 (CC23), phylogroup A, has been predominant among ESBL-producing E. coli isolates from hospitals in Brazil (12). In contrast, E. coli strains belonging to ST224 have been identified in inpatients and outpatients and associated with the production of different clinically important ␤-lactamases, such as NDM-1, KPC-2, and even CTX-M-15 (13)(14)(15), and more recently, the production of CTX-M-8 in E. coli ST224 isolated from dairy buffalo was documented in Brazil (16). Representative E. coli strains belonging to ST410 and ST224 present distinct genetic arrangements upstream of the bla CTX-M-15 gene (Fig.…”
mentioning
confidence: 99%